2023
DOI: 10.1177/23969415231151846
|View full text |Cite
|
Sign up to set email alerts
|

Echolalia as defined by parent communication partners

Abstract: Backgrounds and aims Echolalia, the repetition of previous speech, is highly prevalent in Autism. Research into echolalia has historically assumed a clinical standpoint, with two opposing paradigms, behaviourism and developmentalism, offering differing support and intervention programs. These paradigms offer a multitude of clinical operationalised definitions; despite attempts, there continue to be challenges regarding how echolalia is to be defined. Stepping out of the dichotomous clinically orientated litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Delayed echolalia may be purposeful and meaningful for the speaker and those around them who are privy to the experiential associations. It is also contextual in that the utterances are reminiscent of a previous time when the speech was first heard ( Cohn et al, 2023 ; Sterponi & de Kirby, 2016 ). It has been argued that in all of these ways, delayed echolalia is best understood as varying along a continuum of conventionality ( Prizant, 1983b ; Prizant & Rydell, 1984 ).…”
Section: Autism and Gestalt Language Processingmentioning
confidence: 99%
“…Delayed echolalia may be purposeful and meaningful for the speaker and those around them who are privy to the experiential associations. It is also contextual in that the utterances are reminiscent of a previous time when the speech was first heard ( Cohn et al, 2023 ; Sterponi & de Kirby, 2016 ). It has been argued that in all of these ways, delayed echolalia is best understood as varying along a continuum of conventionality ( Prizant, 1983b ; Prizant & Rydell, 1984 ).…”
Section: Autism and Gestalt Language Processingmentioning
confidence: 99%
“…The assumptions around echolalia are naturally being re-examined as the autistic community and their allies continue to challenge long-held clinical perspectives; the clinical sphere leaves little to no room for voices, regardless of their lived experience, to broaden the narrative around conceptualisations and characterisations of autistic characteristics. Of this changing conceptualisation, recent work by Cohn et al (2023) found that not all parents of children with echolalia agree with clinically oriented definitions, rather, they have their own formulations of a definition and description of echolalia. Specifically, the definition proposed by Cohn et al (2023), informed by parents, moves away from historical clinical definitions which previously included specific components of function, linguistic features, and how echolalia is manifest.…”
Section: Moving Beyond Clinical Perspectivesmentioning
confidence: 99%
“…Of this changing conceptualisation, recent work by Cohn et al (2023) found that not all parents of children with echolalia agree with clinically oriented definitions, rather, they have their own formulations of a definition and description of echolalia. Specifically, the definition proposed by Cohn et al (2023), informed by parents, moves away from historical clinical definitions which previously included specific components of function, linguistic features, and how echolalia is manifest. While the new definition includes these components, it assumes an individualistic stance by suggesting that echolalia may assume a variety of different functions, linguistic features and manifestations, among other components, and that these are largely different for each person with echolalia (Cohn et al, 2023).…”
Section: Moving Beyond Clinical Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations